Time-dependent movements of the hangingwall at the Kiirunavaara mine - Villegas, Tomas; Nordlund, Erling (International Journal of Mining, Reclamation and Environment, 2012)
The hangingwall deformation behaviour at the Kiirunavaara mine has been characterised after several years of collecting surveying data from the ground surface. The monitoring system was implemented to track surface subsidence because the city of Kiruna and the railway are situated on the hangingwall. Data time–displacement and time–velocity curves were used and different stages of deformation behaviour were identified – regressive, progressive and steady state. The movement starts with a regressive behaviour for which subsidence is characterised by continuous deformations. At the end of this stage the movement accelerates, marking the beginning of the progressive behaviour where subsidence becomes more discontinuous. A steady state stage is reached when the strength of the failure surface decreases to the residual value. To predict displacement in the vicinity of the railway, accumulated displacements per year were analysed for several stations for which data for the full regressive stage were available. Displacement tendencies were fitted with quadratic polynomial functions. Therefore, the rate of movement follows a linear trend with a constant acceleration. Finally, a critical horizontal strain limit was determined based on the estimated displacement. Validerad; 2012; 20120129 (tomvil)